INFLUÊNCIA DE REVESTIMENTOS COMESTÍVEIS INCORPORADOS DE PREBIÓTICOS NA QUALIDADE DE MAMÃO PRONTO PARA CONSUMO - Pelissari, Erlany Monteiro Ribeiro (2020)
Papaya is a fruit of economic importance for Brazil and can be eaten fresh or in processed form. Ready-to-eat papaya for consumption is subjected to processing steps, such as peeling and slicing, which can cause physiological changes in plant tissue. The